2014
DOI: 10.1056/nejmoa1400506
|View full text |Cite
|
Sign up to set email alerts
|

Provision of No-Cost, Long-Acting Contraception and Teenage Pregnancy

Abstract: Background The rate of teenage pregnancy in the United States is higher than in other developed nations. Teenage births result in substantial costs, including public assistance, health care costs, and income losses due to lower educational attainment and reduced earning potential. Methods The Contraceptive CHOICE Project was a large prospective cohort study designed to promote the use of long-acting, reversible contraceptive (LARC) methods to reduce unintended pregnancy in the St. Louis region. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
252
1
27

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 327 publications
(284 citation statements)
references
References 11 publications
4
252
1
27
Order By: Relevance
“…Using data from the National Survey of Family Growth, we calculated the percent of teens 15-19 who had ever had sex by race to develop race-specific estimates. This percentage is multiplied by the number teens (15)(16)(17)(18)(19) of each race to estimate the number of sexually active teens by race. The number of sexually active teenagers in the United States is the denominator and the pregnancy rate is the numerator of the race specific estimates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using data from the National Survey of Family Growth, we calculated the percent of teens 15-19 who had ever had sex by race to develop race-specific estimates. This percentage is multiplied by the number teens (15)(16)(17)(18)(19) of each race to estimate the number of sexually active teens by race. The number of sexually active teenagers in the United States is the denominator and the pregnancy rate is the numerator of the race specific estimates.…”
Section: Methodsmentioning
confidence: 99%
“…Given the low number of pregnancies in some years, two-year rates were calculated (2008-2009, 2010-2011, 2012-2013; Table 1). Details of the assessment of unintended pregnancies in CHOICE can be found in Secura et al 15 We examined Black-White disparities in teenage (ages 15-19) pregnancy rates in U.S. population estimates and CHOICE project estimates using two disparities measures: one absolute (rate difference) and one relative measure (rate ratio). Rate difference (RD) is the absolute difference between the unintended teenage pregnancy rates for Blacks (rB) and Whites (rW) and is calculated as rB -rW.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that pregnancy, birth, and abortion rates were low among teenage girls, and women enrolled in a project that removed financial and access barriers to contraception and informed them about the particular efficacy of LARC methods. The observed rates of pregnancy, birth, and abortion were substantially lower than national rates among all US teens [2]. The relative risk of pelvic inflammatory disease (PID) is increased only in the first 20 days after IUD insertion and then returns to baseline, while the absolute risk remains small.…”
Section: Larc For Teensmentioning
confidence: 94%
“…More than 200 million women in the developing world want to prevent pregnancy but are not using modern contraception leaving poor women facing a substantial risk of unintended pregnancy, unsafe abortion, maternal and infant mortality and morbidity [1], whereas in the developed world each year, more than 600,000 teens become pregnant, and 3 in 10 teens will become pregnant before they reach 20 years of age [2]. Teenage pregnancy has also been designated by the Centres for Disease Control and Prevention (CDC) as one of the six Winnable Battles because of the magnitude of the problem and the belief that it can be addressed by strategies that are known to be effective [3].…”
Section: Introduction Global Scenariomentioning
confidence: 99%
“…The study enrolled nearly 10,000 St. Louis women aged 14-45 years and provided nocost contraception for 2 to 3 years. By simultaneously removing these three barriers to commonly used reversible contraceptive methods, the study was able to demonstrate a greater than 50 % reduction in overall abortion and a 56 % reduction in teen pregnancy among women enrolled in the cohort compared to national rates [7,8]. Findings from CHOICE hold promise for reducing unintended pregnancy rates nationwide and abroad.…”
Section: Introductionmentioning
confidence: 93%